PEMBUATAN VIDEO BRANDING THE HIDDEN HERITAGE OF KEDIRI SEBAGAI MEDIA PROMOSI DIGITAL INDUSTRI TENUN IKAT BANDAR KIDUL KEDIRI - Megasari Noer Fatanti; Kun Sila Ananda; Ananda Dwita Yuniar; Pramana Herjati Putra; Rohmatin Rohmatin; Hasna Bararah (LPPM Universitas Trunojoyo Madura, 2022)
Kediri has various tourism potential, both natural, historical, and cultural tourism. One historical heritage still preserved now is the ikat craft centre in Bandar Village, Mojoroto District, Kediri City. The woven product known as the Bandar Kidul Tenun Ikat (TIBK) has been able to last more than 50 years. One of the advantages of this woven cultural product is that it is still produced traditionally, known as a non-machine loom (ATBM). Until now, there are around 15 artisans and ikat weaving business owners who are still actively producing. However, often the ikat fabrics produced can only compete in the local market. This condition is the main problem partners face, which has implications for the decline in income turnover and the cessation of production for several artisans. Based on this situation, the community service’s team of Universitas Negeri Malang provided an alternative solution to make a branding video,